Self‐reported wellbeing and health‐related quality of life of Aboriginal and Torres Strait Islander people pre and post the first wave of the COVID‐19 2020 pandemic - Alana Gall; Abbey Diaz; Gail Garvey; Kate Anderson; Daniel Lindsay; Kirsten Howard (Elsevier, 2022)
Abstract Objective: Quantify change in wellbeing and health‐related quality‐of‐life (HRQoL) in Aboriginal and Torres Strait Islander adults pre and post Australia's initial COVID‐19 lockdown. Methods: Aboriginal and Torres Strait Islander adults completed an online survey at Time 1 (October-November 2019; before the initial Australian COVID‐19 outbreak) and Time 2 (August-September 2020; after the first Australian lockdown). We assessed wellbeing using a visual analogue scale (VAS) and HRQoL using the Assessment of Quality of Life (AQoL‐4D) instrument. Participants who completed both surveys (n=42) were included to quantify change in outcomes over time and by comorbidity and demographic factors. Results: Mean reduction in wellbeing over time was 6.4 points (95%CI −14.2 to 1.4) and was associated with age (18-54yo), financial instability and mental health comorbidity. Mean reduction in HRQoL over time was 0.06 (95%CI −0.12 to 0.01) and was associated with financial instability, high physical comorbidity level and mental health comorbidity. Conclusions: Aboriginal and Torres Strait Islanders aged 18-54yo, who were financially unstable or had elevated comorbidity during COVID lockdowns experienced greater reductions in wellbeing and HRQoL. Implications for public health: As the COVID‐19 pandemic continues in Australia, both urgent and forward planning is needed, especially for the priority groups identified.